1995
DOI: 10.1111/j.1525-1594.1995.tb02289.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Clinical Evaluation of an Adsorbent Column (BM–01) of Direct Hemoperfusion Type for (β2–Microglobulin on the Treatment of Dialysis‐Related Amyloidosis

Abstract: The clinical efficacy and safety of a beta 2-microglobulin (beta 2M) adsorbent column, BM-01, on the treatment of dialysis-related amyloidosis were investigated in 7 hemodialysis patients for more than 6 months. The percent reduction of serum beta 2M was more than 60-70%, and the level at the end of each session was less than 10 mg/L in almost all patients. The amount of beta 2M removed was calculated as more than 200-300 mg/session. The results demonstrated that BM-01 performed very well for removing beta 2M,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Many groups have reported the clinical use of this column for long-term hemodialysis patients, and its usefulness and efficacy have been demonstrated. [19][20][21][22][23] However, there have been few reports on the bioincompatibility of this column, because it has been in clinical use with hemodialysis treatment for only a few years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many groups have reported the clinical use of this column for long-term hemodialysis patients, and its usefulness and efficacy have been demonstrated. [19][20][21][22][23] However, there have been few reports on the bioincompatibility of this column, because it has been in clinical use with hemodialysis treatment for only a few years.…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal circulation was maintained for 4 h by connecting the BM-01 for direct hemoperfusion (DHP) in series to the arterial side before the dialyzer, as described elsewhere. [19][20][21][22][23][24] Production of monoclonal antibody against MPO Plasma levels of MPO were measured by an enzyme immunoassay (EIA) established in our laboratory. MPO purified from human peripheral blood leukocytes was used to immunize mice.…”
Section: Adsorbent Columnmentioning
confidence: 99%
See 1 more Smart Citation
“…One report found that the ineidence of dialysis-related amyloidosis had decreased signifieantly since the introduction of high-flux membrane dialyzers; however, no consensus has yet been reaehed. Nevertheless, for [24]. An adsorbent column of the direct hemoperfusion type that was developed for the elimination of ß2-m appeared to be clinically useful [24].…”
Section: Approaches To Prevention and Treatmentmentioning
confidence: 99%
“…Nevertheless, for [24]. An adsorbent column of the direct hemoperfusion type that was developed for the elimination of ß2-m appeared to be clinically useful [24]. van Ypersele et al [25] compared the accumulation of ß2-m in the serum of patients treated with dialyzers using a high-flux membrane (AN-69) versus those treated with dialyzers using a cuprophane membrane.…”
Section: Approaches To Prevention and Treatmentmentioning
confidence: 99%